Enhancing Wireless Communication Learning Through Interactive Hands-On Trainer Applications Using 433 MHz LoRa Networks - Aslinda Zamah Shari; Fazida Adlan; Guan Chengg Wong (Malaysia Journal of Invention and Innovation, 2025)
This study presents an innovative hands-on trainer using 433 MHz LoRa networks to enhance learning in the DEP50063 Wireless Communication course at Politeknik Sultan Salahuddin Abdul Aziz Shah. The trainer addresses the challenge of outdated lab equipment, which limits student’s understanding of key wireless concepts such as frequency, distance, low power and environmental impact. Designed to link the gap between theory and practice, the trainer integrating ESP32 boards, LoRa SX1278 modules and adjustable antennas to provide an interactive and practical learning experience. The main objectives are to improve student engagement, develop skills in wireless IoT technology and make practical sessions more efficient for lecturers. Positive feedback from students and lecturers highlights significant improvements in understanding and applying wireless communication concepts, meeting Course Learning Outcome 2 (CLO 2) and Program Learning Outcome 5 (PLO 5). The trainer also demonstrates strong commercialization potential, being cost-effective, scalable and applicable to various industries such as agriculture and smart cities. In conclusion, the 433 MHz LoRa trainer is a valuable educational tool that equips students with the skills needed for real-world challenges while enhancing teaching and learning efficiency.